Genetic studies of Northern Goshawks (Accipiter gentilis): genetic tagging and individual identification from feathers, and determining phylogeography, gene flow and population history for Goshawks in North America - Bayard de Volo, Shelley, author; Antolin, Michael F., advisor; Reynolds, Richard T., committee member; Douglas, Marlis R., committee member; Burnham, Kenneth P., committee member (Colorado State University. Libraries, 2008)
The Northern Goshawk (Accipiter gentilis) is a large, highly mobile, mostly nonmigratory and widespread forest raptor. It ranges across the Boreal forests from Alaska to Newfoundland, and south into forests of the Great Lakes, and montane regions of the Appalachian, Cascade, Sierra Nevada, Rocky Mountain, and Sierra Madre Occidental. There has been much interest in the population and taxonomic status of Northern Goshawks, especially for populations occurring west of the 100th meridian. The objectives of my dissertation were to (1) determine whether alternative methods to capture-recapture methods were feasible; and (2) evaluate the genetic relationships among goshawk populations across their continental U.S. range. The genetic "marking" studies (Chapters 1 and 2) provided feasible and cost-effective alternative methods for capture-recapture, and are logistically easier to implement. If used, these methods have the potential to standardize the collection of demographic data across the species' range. Assessment of the genetic status among goshawks (Chapter 3) indicated populations are subdivided at a regional scale, with some gene flow within and among regions.
Department Head: William K. Lauenroth.